Data from: All roads lead to home: panmixia of European eel in the Sargasso Sea - Als, Thomas D; Hansen, Michael M; Maes, Gregory E; Castonguay, Martin; Riemann, Lasse; Aarestrup, Kim; Munk, Peter; Sparholt, Henrik; Hanel, Reinhold; Bernatchez, Louis (Data Archiving and Networked Services (DANS), 2020)
European eels (Anguilla anguilla) spawn in the remote Sargasso Sea in partial sympatry with American eels (Anguilla rostrata), and juveniles are transported more than 5,000 kilometres back to the European and North African coasts. The two species have been regarded as classic textbook examples of panmixia, each comprising a single, randomly mating population. However, several recent studies based on continental samples have found subtle, but significant, genetic differentiation, interpreted as geographical or temporal heterogeneity between samples. Moreover, European and American eels can hybridize, but hybrids have been observed almost exclusively in Iceland, suggesting hybridization in a specific region of the Sargasso Sea and subsequent non-random dispersal of larvae. Here, we report the first molecular population genetics study based on analysis of 21 microsatellite loci in larvae of both Atlantic eel species sampled directly in the spawning area, supplemented by analysis of European glass eel samples. Despite a clear East-West gradient in the overlapping distribution of the two species in the Sargasso Sea, we only observed a single putative hybrid, providing evidence against the hypothesis of a wide marine hybrid zone. Analyses of genetic differentiation, isolation by distance, isolation by time and assignment tests provided strong evidence for panmixia in both the Sargasso Sea and across all continental samples of European eel after accounting for the presence of sibs among newly hatched larvae. European eel has declined catastrophically, and our findings call for management of the species as a single unit, necessitating coordinated international conservation efforts. Als et al. 2011 data fileData file with genotype data for 1010 European glass eel, 271 European eel larvae from the Sargasso Sea and 117 American eel larvae from the Sargasso Sea. Individual number: Sample code for each individual Species.ID: AA = European eel, AR American eel Transect/region: Transect in the Sargasso Sea or geographical ...